RHETORICAL ARGUMENTATION IN MODERN PUBLIC SPEAKING - Vorobiova, Alla; Shaposhnykova, Iryna; Hlushchenko, Iryna; Shvets, Tatiana; Koval , Viktoriia (Revista Inclusiones, 2019)
This research addresses modern tendencies in rhetorical argumentation. The theoretical rationale of the study lies in the different approaches to studying the forms of arguments and their content. The study showed that the compositional perfection of argumentation can be successfully implemented where sequential deployment of the logical arguments and emotional reasoning achieve such goals as audience acquisition, acceptance and planned response. The argumentative system chosen allows for distinguishing the contemporary aspects of persuasive strategies in public appearance. To obtain an understanding of recent trends in argumentation, an analysis was performed of political speeches delivered by the presidents of Belarus, Kazakhstan, China, Ukraine and the United States during the 70th session of the United Nations General Assembly (September 15, 2015). As a result of this inquiry into the rhetorical discourse we tried to facilitate students’ learning of argumentation, to develop their ability to critically analyse sample texts, to give them to understand what arguments and reasoning are more preferable. With the methodology of cliché (sample text) replenishment, we describe a way to engage students in studying rhetorical discourse, help them to develop the ability to analyse modern argumentation critically in the real-world contexts.